Annual acknowledgement of manuscript reviewers. Issue 1 (December 2016) - Minas, Harry
Abstract With the proliferation of journals and the ever-increasing demands on the time and expertise of reviewers it has become increasingly difficult for editors to get high quality and timely reviews. On behalf of authors as well as the Journal the editors of International Journal of Mental Health Systems would like to thank all our reviewers who have made an indispensible contribution to the journal in Volume 9 (2015).